The effects of intellectual capital on information communication technology firm performance: A moderated mediation analysis of environmental uncertainty - Hoang Thanh Nhon; Bui Quang Thong; Ngo Quang Trung (Cogent Business & Management, 2020)
The impact of intellectual capital on firm performance is one of the key aspects of strategic management. This is particularly crucial for firms in the high-tech or service sectors. Intellectual capital dimensions, including human, organisational and social capital, are key to developing outstanding performance. From a strategic management perspective, there are still debates on the interrelationships between these dimensions, and on the moderating role of environmental uncertainty on their impacts on performance. In the context of an unstable environment like Vietnam, this study involved a survey of 350 information communication technology (ICT) firm's directors and managers, which was used to analyse the impacts of intellectual capital dimensions on firm performance, the indirect effects of organisational capital on performance via human and social capital, and the moderating role of environmental uncertainty. Findings indicate that all dimensions of intellectual capital had direct impacts on firm performance. In addition, we found that the human and social capital mediated significantly the relationship between firm performance and organisational capital, and the environmental uncertainty moderated significantly the relationship between intellectual capital dimensions and firm performance.
Keywords: 650; Firm performance; intellectual capital; human capital; social capital; organisational capital; environmental uncertainty; mediate and moderate